A Field Study For Designing An Integrated Framework To Enhance Information Security In The E-Management Environment - Shuaib Mohammed Sharif Abdo; Asmaa Rasheid Hameed (Academia Open, 2026)
General Background: The expansion of digital transformation in governmental institutions has increased reliance on electronic management systems, making information security a strategic priority. Specific Background: Despite the adoption of global standards such as ISO 27001, NIST, COBIT, and Zero Trust, existing approaches often separate technical and administrative dimensions, limiting practical implementation in e-management environments. Knowledge Gap: There remains a lack of a unified framework integrating technological, governance, and human-cultural aspects tailored to institutional contexts. Aims: This study develops an integrated information security framework combining technical infrastructure, governance policies, training, and security culture using Design Science Research Methodology. Results: Empirical analysis using SEM-PLS shows that organizational maturity (β=0.67) and technical measures (β=0.59) are primary drivers, while policies and training (β=0.44) and security culture (β=0.18) play supporting and mediating roles, explaining 74% of variance. Implementation increased readiness index from 65.2 to 83.9 and reduced incidents by 31%. Novelty: The study proposes a holistic, empirically validated framework integrating technical, administrative, and cultural dimensions within a single architecture. Implications: The framework provides actionable guidance for policymakers to establish unified governance structures, strengthen security culture, and deploy adaptive mechanisms in electronic management systems. Highlights:• Holistic Model Integrates Governance Structures With Technological Safeguards and Human Factors• Empirical Evidence Explains Major Variance in System Protection Performance• Framework Application Shows Measurable Increase in Readiness and Reduced Incident Frequency Keywords: Information Security, E-Management, Cybersecurity Framework, Security Culture, Organizational Maturity